The Improving Activities, Critical Thinking Skills And Ppkn Content Learning Outcomes Using The Panda Model - Prameswari, Dyah; Cinantya, Celia (Berpusi Publishing, 2023)
The research was motivated by the problem of low student activity, critical thinking skills and student learning outcomes with Civics content which was caused by one-way learning activities, there were no learning activities that guided critical thinking and learning was not meaningful for students. An attempt to solve this problem is through the application of the PANDA model. The research carried out aims to describe teacher activities, analyze student activities, critical thinking skills and student learning outcomes. The approach is carried out using a qualitative and quantitative approach in the PTK type. The research subjects were students of IVA SDN Melayu 6 Banjarmasin with a total of 16 students. The research instruments were observation sheets of teacher activities, student activities and critical thinking skills. The research results prove, The teacher's activity at meeting IV received a very good category. Classical student activities obtained 94% at meeting IV. Students' classical critical thinking skills were obtained at meeting IV at 88%. And student learning outcomes at meeting IV classically obtained 94% at meeting IV. It is recommended that the PANDA model be used as a reference in implementing innovative learning models.